Desalination and Distillation Program Using Appropriate Technology as an Effort to Alleviate the Clean Water Crisis on Messah Island, Manggarai Regency, East Nusa Tenggara - Widianto, Maria Tesalonika Ajeng Widiastari; Purwanti, Tari (Sabda: Jurnal Kajian Kebudayaan, 2021)
Clean water is not just a necessity, but the basic right of every living creature, including humans. However, in reality, not all regions in Indonesia enjoy adequate access to clean water, and Messah Island is one example. The people of Messah Island face serious challenges in accessing clean water due to their geographical location and extreme climate conditions, which force them to rely on sea water as a daily source of air. The research results detail that there is a solution that can be implemented to overcome the clean water crisis on Messah Island, namely through a seawater distillation and desalination program. Distillation aims to translate water, while desalination processes seawater into fresh water. This second method can be an effective solution to meet the need for clean water on this island. The importance of the government's role in this effort cannot be ignored. The government is expected to not only provide distillation and desalination facilities, but also support understanding regarding sustainable management of community clean water. Only with active government involvement and cooperation between stakeholders can the clean water crisis on Messah Island be overcome and the basic right to clean water can be guaranteed for all communities.Keywords: Clean water, Distillation, Desalination, Messah Island, Clean water crisis